Estudo epidemiológico da brucelose em fêmeas bovinas adultas da regional Rio das Antas, Goiás - Montes, Thiago Menegazzo (2017)
Brucellosis is an infectious-contagious and zoonotic disease caused by bacteria of the genus Brucella. It is an endemic disease in Brazil, with a variable prevalence and it mainly affects the reproductive tract of the animals, resulting in several damages in the countryside, industry and public health. This research aimed to determine the prevalence of brucellosis in adult cows in the Rio das Antas Regional (Goiás), its spatial distribution and the factors associated with this disease. A total of 95 farms were randomly selected for blood sampling in cows over 24 months of age, totalizing 992 samples. These samples were submitted to the Buffered, Acidified Plate Antigen test, and for those positive cases, to the 2-Mercaptoethanol test. An epidemiological survey was applied to evaluate the risk factors for brucellosis in each farm. There was an apparent prevalence of 13.68% [7.49 - 22.26] for farms and 2.11% [1.32 - 3.22] for animals. In bovine females, the multiple logistic model for brucellosis risk factors detected a significant effect for the B19 vaccine variable (OR = 2.85; IC [1.05 – 7.04]). For these results, it can be stated that bovine brucellosis in herds and animals is considered high in the evaluated region, with a wide spatial distribution, dispersed throughout the studied territory and in all production systems. Among the factors associated with the risk of brucellosis in adult bovine females, vaccination is associated.